Subsurface flow and free water surface flow constructed wetland with magnetic field for leachate treatment - Md. Sa'at, Siti Kamariah (2006)
This study conducted using two-stage lab-scale Subsurface Flow (SSF) and Free Water Surface (FWS) constructed wetland under influence of magnetic field to treating the leachate. The leachate samples were pre-treated with magnet circulation with strength 0.55T. The constructed wetlands were planted with Limnocharis flava (yellow bur-head) and Eichhornia crassipes (water hyacinth). The performance of the system determined by suspended solid, nutrient (ammonia and phosphate), heavy metal (Iron and Manganese) removals and uptake by root and leaves of constructed wetland plants. From the analysis, planted system shows higher removal compared to unplanted system. The result shows great removal efficiency with 98.7% NH3-N, 90.2% PO43-, 98.7% Fe, 92.5% Mn and 94.3% SS removal. At the end of study, the plants harvested and analyzed for heavy metals uptake by plants. The results showed that Fe uptake on leaves greater than on roots while Mn uptake on roots is greater than in leaves. For Limnocharis flava for example, 54% Fe uptake by leaves while 44% uptake by roots and Mn uptake by roots was 51% while 34% by leaves. This study concludes that SSF-FWS constructed wetland with magnetic field can improve the leachate quality.